Enhanced Cycle Stability of Low‐Cost Na‐Rich Metallic NaCl Electrode for Advanced Na‐Ion Batteries. (27th November 2022) - Moeez, Iqra; Susanto, Dieky; Park, Jae‐Ho; Kim, Ji‐Young; Lim, Hee‐Dae; Chung, Kyung Yoon
Abstract: Sodium‐rich metallic Na x + z has received significant attention as a low‐cost alternative to the conventional electrode materials used in Li‐ion batteries. However, the poor cyclability of Nax Cl remains a major challenge to its practical application. Here, a simple method is developed for improving the electrochemical performance of Nax Cl by controlling the upper limit of cut‐off voltage. It is demonstrated that additional Na‐vacancy defects can be introduced in the NaCl structure during the high‐voltage activation process at 4.5 V. The structure then accommodates more sodium ions during the next discharge, resulting in increased capacity. At the same time, Cl‐ions released by NaCl decomposition are oxidized to form Cl‐based organic species at the active material interfaces. This plays a crucial role in protecting the NaCl electrode from undesired side reactions at high voltage. In short, this control of the charging protocol helps to induce more vacancies in the NaCl structure, as well as form stable interphases on the electrode surface, contributing to the increased capacity and enhanced cycle stability. This study will help in exploring a new approach for developing low‐cost and high‐capacity electrode material, which can potentially be applied in future energy‐storage systems. Abstract : A simple strategy of over‐charging activation is proposed to enhance the cycle stability and capacity retention of metallic Nax Cl: x > 1 electrode with the introduction of additional Na‐vacancies and formation of protective interphase, which provides new thoughts for developing cost‐effective high‐voltage electrodes for the application of sodium‐ion batteries in future large‐scale energy storage systems.